Magnetic Integration of LCC Compensation Topology with Minimized Extra Coupling Effects for Wireless EV Charger. (May 2017) - Deng, Junjun; Pang, Bo; Shi, Wenli; Wang, Zhenpo
Abstract: Wireless electric vehicle charger has become increasingly popular because of its improved convenience and safety. The recently proposed doubled-sided LCC compensated topology and bipolar magnetic coupler structure have promoted the comprehensive performance of the wireless power transfer (WPT) system. Furthermore, the idea of integrating the magnetic components in the LCC compensated WPT system has been proposed for reducing the bulk. However, the extra inter-couplings between the adjacent coils are also introduced, which complicates the parameters design and the characteristic analysis. In this paper, a new integration method is presented for wireless EV charger adopting LCC compensation networks along with bipolar coupler. The impact of the extra couplings is evaluated through circuit analysis and simulation. The finite element analysis (FEA) tool is utilized to simulate the extra coupling effects of the compensated coil, which leads to the proposed integration coupler structure. At last, a 550 mm × 500 mm with a nominal 150-mm-gap and 6.6-kW-power prototype, has been built and tested. A peak efficiency of 95% from a DC power source to the load is achieved.